HUBUNGAN KREATIVITAS GURU DENGAN MINAT BELAJAR SISWA KELAS V SDN 82 SINGKAWANG - Anggreini, Septi; Rosmaiyadi; Abd.Basith (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Teacher creativity in the learning process has a central role in helping increase students' interest in learning. Through creative and fun teaching methods, it is hoped that teachers can help increase students' interest in learning at school. Interest in learning is important to encourage students to be more active and active in achieving their learning goals. This research aims to determine the relationship between teacher creativity and the learning interest of class V students at SDN 82 Singkawang. The population in this study was 47 students, namely students in classes Va and Vb. Meanwhile, the sample is the total number of the population, namely 47 students. The sampling technique uses saturated samples or total sampling. Research data was obtained using a questionnaire. The results of data analysis show that there is no relationship between teacher creativity and student interest in learning. This can be seen from the correlation hypothesis test which shows that the normality of the teacher creativity questionnaire and the student interest questionnaire are not normally distributed with the decision of a sig value smaller than 0.05, namely 0.00 < 0.05, meaning that the data obtained is not normally distributed. Judging from the calculation results of the data from the two questionnaires which were not normally distributed, the researcher calculated using the Spearman Rank correlation analysis technique with results of 0.203 > 0.05 with a significance level of a= 0.05 with the number of students (n)= 47 students, then Ho was accepted, meaning that there was no significant relationship between variables X (teacher creativity) and Y (interest in learning) with a very low level of relationship. Therefore, the research results show that there is no significant relationship between teacher creativity and the learning interest of class V students at SDN 82 Singkawang.